Reflections on critical museology : inside and outside museums - Lorente, Jesús Pedro (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Reflections on Critical Museology: Inside and Outside Museums offers a reflective and reflexive re-assessment of museum studies and the first wide-ranging account of critical museology. Drawing on an extensive range of examples from museums and across the museological literature, which are purposefully representative of very different cultural backgrounds, the book issues a plea for critical thinking in and about museums. The various institutions covered and the plural analytical standpoints offer a broad interdisciplinary approach by intermingling art history, anthropology, sociocultural theories, and heritage studies. The result is not claimed as a universal or all-encompassing account, but a subjective review produced by J. Pedro Lorente, an art critic and historian who has been writing extensively about 'critical museology' in different languages for many years. Lorente offers a fascinating synopsis of his ideas in this extremely valuable short book, looking inside and outside museums, combining practice and theory, whilst also relating both to the work of museum professionals and to a range of publications by academics, including those from other research fields. Reflections on Critical Museology: Inside and Outside Museums will be essential reading for university students and academics working in museum studies and cognate disciplines, such as art history, anthropology and cultural studies"--
Academic echoes of the label 'critical museology' and its referents -- Museums in question, self-questioning museums -- Variety and plurality in spatial and interpretive discourse -- Re-presentations of historical legacies in times of self-reflexive museology -- Final (self-) critical considerations.
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Philosophy; Museum techniques -- Philosophy